Case report: anaesthetic management of radical gastrectomy for gastric cancer associated with anti-N-methyl-D-aspartate receptor encephalitis - Lei Ding; Hongyu Tan; Ziyu Li; Jiafu Ji; Xuejun Song (BMC Anesthesiology, 2017)
Abstract Background Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is a rare neurological disorder that is caused by the production of antibodies against NMDARs. As many anaesthetic drugs interact with NMDARs and may worsen the disease and because the disease poses risks, such as cardiovascular events, hyperthermia and respiratory insufficiency, while under anaesthesia, administering anaesthesia to patients with this disorder is clinically challenging. Case presentation A 55-year-old man with gastric cancer associated with anti-NMDAR encephalitis who was diagnosed 8 months prior was admitted to Peking University Cancer Hospital for tumour resection. Before surgery, the patient’s symptoms had been successfully controlled via aggressive immunotherapy. Radical gastrectomy was performed under general anaesthesia induced with remifentanil, propofol, and cisatracurium and maintained with sevoflurane and remifentanil. The patient had a favourable recovery without any adverse symptoms or post-operative complications. Conclusions Adequate preparation for surgery is essential for the anaesthetic management of patients with anti-NMDAR encephalitis. These rare patients may benefit from general anaesthesia induced using remifentanil, propofol and cisatracurium and maintained using sevoflurane and remifentanil. Additionally, the use of NMDA antagonists, such as ketamine, nitrous oxide and tramadol, should be avoided.